Personal Major Events and Reactions to Retirement: Preliminary Findings - MacLean, Michael J. (Canadian Journal of Counselling and Psychotherapy, 2012)
The lifestyle concept of Personal Major Events is proposed as a measure to predict an individual's reactions to retirement. The personal major events of 44 retired professional men were categorized into the mutually-exclusive categories of work events, family events, and leisure events. Preliminary findings suggest a siginificant negative relationship between the work proportion of personal major events and adjustment to and enjoyment of retirement. A significant positive relationship was found between the family proportion of personal major events and enjoyment of and prior attitudes to retirement. Implications of these findings suggest that the concept of personal major events is relevant for pre-retirement planners and as a research area in social gerontology.